Socio-network group formation in the context of evaluating the national projects implementation - V. S. Bogdanov; A. S. Smirnova; M. D. Burdyukova (Цифровая социология)
This article presents the results of an online research of socio-network group formation within the of national projects’ implementation. By socio-network group formation, we mean the activation and organisation of information and communication interaction of users of online social networks in the context of discussing specific regional problems and developing constructive solutions to solve them.The database of posts and comments collected from the social network Vkontakte was the empirical basis of the study. The data was collected from 4 most relevant national projects: “Healthcare”, “Housing and urban environment”, “Safe and high-quality highways” and “Education” in 12 regions of the Russian Federation. These projects have been selected according to their socio-cultural modernisation level.The study has found that each region, according to its socio-cultural modernisation level, has its nature of discussion and solving existing problems, socio-network group formation. In all regions, there is a low level of population satisfaction of projects’ implementation and the specific regional problems solutions. The most pressing problems and barriers specific to each of the national projects have been identified. It has been noted that in most of communities, there is either no feedback on the population complaints or this feedback has the formal replies form that do not lead to real actions by the problem solving actors. National project realisers consider the population only as a recipient, but not as a problem-solving actor (partner). The information posted in official publics is most often declarative in nature.It has been concluded about the low level of development of regional and municipal administration systems, and the weak understanding of local problems and needs by the federal center.